Hadith #3399 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Rafi' bin Khadij bin Rafi'; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Tarq bin 'Abdur Rahman طارق بن عبد الرحمن البجلي الأحمسي الكوفي (Sunan Abi Dawud)
My uncle sent me and his slave to Sa’id ibn al-Musayyab. We said to him, there is something which has reached us about sharecropping. He replied: Ibn Umar did not see any harm in it until a tradition reached him from Rafi’ ibn Khadij. He then came to him and Rafi’ told him that the Messenger of Allah (ﷺ) came to Banu Harithah and saw crop in the land of Zuhayr. He said: What an excellent crop of Zuhayr is! They said: It does not belong to Zuhayr. He asked: Is this not the land of Zuhayr
Grade: Sahih

Hadith #3740 - Sunan Abi Dawud - Aban bin Tarq أبان بن طارق; Darst bin Ziyad درست بن زياد العنبري; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nafie' نافع مولى ابن عمر; Tarq bin 'Abdur Rahman طارق بن عبد الرحمن البجلي الأحمسي الكوفي (Sunan Abi Dawud)
when one of you is invited to a meal, he must accept. If he wishes he may eat, but if he wishes(to leave), he may leave.
Grade: Sahih